Indonesian mental revolution movement as a key-drive for accelerating the quality of public services: from idea to implementation - Pandiangan, Freddy; Ningrum, Sinta; Karlina, Nina; Mulyawan, Rahman; Madani, Muhlis; Yusuf, Muhammad (Department of Government Studies Universitas Muhammadiyah Makassar, 2024)
This research aims to find out the implementation of a mental revolution that encourages the acceleration of innovation and digitalization of public services through the implementation of e-government to build a clean, effective, democratic and trusted government. The research design uses descriptive qualitative research by analyzing policy documents. This article examines the evolution of public service innovation policies in Indonesia related to the mental revolution initiative. The documents reviewed are laws, government regulations, ministerial regulations, and policy documents related to public service innovation and transformation, as well as e-government from January 2014 to May 2024. The results showed that since the launch of the National Movement for Mental Revolution, through the Indonesia Serves program, there has been an acceleration of the process of developing public service digitization innovations. This initiative encourages the acceleration of changes in the quality of public services by accelerating changes in the mindset, attitudes, and behavior of state civil apparatus to produce service innovations that improve the quality of public services. The acceleration of innovation development through e-government and public service digitalization can be realized with budget support, human resource readiness, sustainable policy commitment, and strong leadership in supporting the sustainability of holistic public service innovation.